Regional co-evolution of firm population, innovation and public research? Evidence from the West German laser industry - Ann-Kathrin Blankenberg; Guido Buenstorf (Philipps-University Marburg, Department of Geography, 2015)
We explore the regional co-evolution of firm population size, private-sector patenting and public research in the empirical context of German laser research and manufacturing over more than 40 years from the emergence of the industry to the mid-2000s. Our qualitative as well as quantitative evidence is suggestive of a co-evolutionary process of mutual interdependence rather than a unidirectional effect of public research on private-sector activities.
Keywords: B52; O31; R12; 330; co-evolution; innovation systems; vector autoregression; laser technology